Search for decaying dark matter in the Virgo cluster of galaxies with HAWC - Albert, A.; Alfaro, R.; Alvarez, C.; Arteaga-Velázquez, J. C.; Ayala Solares, H. A.; Babu, R.; Belmont-Moreno, E.; Caballero-Mora, K. S.; Capistrán, T.; Carramiñana, A.; Casanova, S.; Cotzomi, J.; et al. (Physical Review D, 2024)
The decay or annihilation of dark matter particles may produce a steady flux of very-high-energy gamma rays detectable above the diffuse background. Nearby clusters of galaxies provide excellent targets to search for the signatures of particle dark matter interactions. In particular, the Virgo cluster spans several degrees across the sky and can be efficiently probed with a wide field-of-view instrument. The High Altitude Water Cherenkov (HAWC) observatory, due to its wide field of view and sensitivity to gamma rays at an energy scale of 300 GeV-100 TeV is well-suited for this search. Using 2141 days of data, we search for γ-ray emission from the Virgo cluster, assuming well-motivated dark matter substructure models. Our results provide some of the strongest constraints on the decay lifetime of dark matter for masses above 10 TeV.
CRIS-Team Scopus Importer:2024-03-29